GIS-Based Assessment on the Need and Accessibility of Bus Stops at UTHM Pagoh Campus - SUHAIMI, SYUHADA SUZANA; SARIF, ABD SUKOR (Progress in Engineering Application and Technology, 2025)
The absence of bus stop shelters in Universiti Tun Hussein Onn Malaysia (UTHM) Pagoh Campus is being an issue that all students faced especially for bus users. This study addresses the critical issue of inadequate bus stop shelters which significantly impacts accessibility, comfort, and safety for students and other users. The absence of proper shelters exposes commuters to weather conditions like heavy rain and heat, negatively affecting their transportation experience. This problem becomes particularly acute during peak hours when passenger volumes surge dramatically. The research was conducted with three primary objectives: first, to evaluate current bus stop conditions; second, to analyze shelter demand based on weather challenges and user needs; and third, to map bus stop coordinates using Geographic Information System (GIS) technology for improvement proposals. The study employed a mixed-methods approach combining quantitative surveys with 511 student respondents, detailed field observations, and spatial analysis using GIS software. Findings revealed that 99% of respondents confirmed the lack of shelters at all bus stops, with Stops 1, 2, and 5 identified as most critical due to their high utilization rates. An overwhelming 98% of participants expressed an urgent need for shelter installation, additional seating, and clearer signage. GIS mapping successfully identified locations for shelter installations through spatial data analysis and user needs assessment. The study proposes medium-sized bus stop designs emphasizing accessibility, comfort, and weather resistance. These recommended improvements aim to enhance campus community welfare, support sustainable transportation systems, and serve as a model for other educational institutions. Implementation of these proposals aligns with UTHM's commitment to inclusive infrastructure development and sustainable campus practices.